THYROID FUNCTION ABNORMALITIES IN PRETERM INFANTS: A COHORT STUDY IN A CHILDREN’S HOSPITAL - K, Sidhu Manpreetaljit; Lee, Yong Hong; Lim, Song Hai (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Congenital hypothyroidism (CH) is a significant condition included in our national newborn screening programs based on raised cord thyroid stimulating hormone (TSH). However, in preterm infants, initial screening may miss elevated TSH. Hence, re-screening is recommended in most CH screening guidelines. This study aims to evaluate thyroid function abnormalities in preterm infants taken during re-screening. METHODOLOGY This is a retrospective study. All preterm infants admitted to our neonatal intensive care unit (NICU) between June 1, 2024 to February 1, 2025, with at least one thyroid function test (TFT) done will be included. Clinical parameters were extracted from the department's electronic medical record, and TFTs were retrieved from electronic laboratory records. The TFTs, including TSH and free thyroxine (fT4), were performed according to our NICU protocol, whereby: Infants <32 weeks: initial TFT at 4 weeks postnatally, repeated fortnightly. Infants ≥32 weeks: initial TFT at 36 weeks corrected age, repeated biweekly. RESULT There were 5,561 live births during the study period, of which 190 were preterm. A total of 120 preterm infants (55% male and 44% female) had at least one TFT done, of which 25 infants (20.8%) had abnormal TFTs. Transient hyperthyrotropinemia was the most common abnormality (15.8%), followed by transient hypothyroxinemia (3.3%). One case of primary hypothyroidism (1.7%) was diagnosed at the postnatal age of 40 weeks and required thyroxine treatment, giving rise to CH incidence of 1:120 in this cohort. CONCLUSION The majority of preterm infants with abnormal thyroid function had transient conditions and did not warrant treatment. Our CH incidence among preterm infants is high, which may be due to a smaller cohort. Our findings support the ongoing re-screening for CH in preterm infants. However, TFTs should be interpreted with caution to avoid over-treatment of transient thyroid dysfunction.